2011
DOI: 10.3109/09513590.2011.583958
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone reduces central obesity in polycystic ovary syndrome women

Abstract: Pioglitazone has beneficial effects on central obesity of the patients with polycystic ovary syndrome but other clinical consequences of the syndrome may not improve with the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…The metformin-treated patients showed a reduction in the W/H ratio, which contradicts the findings of Morin-Papunen et al, in which waist to hip ratio remained the same after treatment 19 and similar results occurred in the Pioglitazone-treated group reported by Asadipooya and colleagues 20 .…”
Section: Resultscontrasting
confidence: 64%
“…The metformin-treated patients showed a reduction in the W/H ratio, which contradicts the findings of Morin-Papunen et al, in which waist to hip ratio remained the same after treatment 19 and similar results occurred in the Pioglitazone-treated group reported by Asadipooya and colleagues 20 .…”
Section: Resultscontrasting
confidence: 64%
“…It also decrease fatty acid release, suppress gluconeogenesis and reduce tumor necrosis factor a disruption of insulin activity [49]. Along with a reduction in insulin resistance, these agents also significantly reduce the central obesity in DM, a common trait found in PCOS also [50,51]. Although, effective in induction of ovulation and regularising the menstruation in PCOS patients [52,53], it has its limitations in women seeking pregnancy, where metformin stands out to be a better and safer alternative [52].…”
Section: Discussionmentioning
confidence: 99%
“…61 The 63,64 Recent studies have demonstrated lower GIP levels in obese women with PCOS. 65,66 Given that insulin resistance is of pathophysiological relevance to the endocrine and metabolic dysfunction of PCOS, the therapeutic benefit of incretin therapy in this population is plausible.…”
Section: Thiazolidinedionesmentioning
confidence: 99%